2019
DOI: 10.3390/en12234593
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Fuel Cell Technology for the Sustainable Future of Stationary Applications

Abstract: The climate changes that are becoming visible today are a challenge for the global research community. The stationary applications sector is one of the most important energy consumers. Harnessing the potential of renewable energy worldwide is currently being considered to find alternatives for obtaining energy by using technologies that offer maximum efficiency and minimum pollution. In this context, new energy generation technologies are needed to both generate low carbon emissions, as well as identifying, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
123
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 299 publications
(125 citation statements)
references
References 57 publications
0
123
0
2
Order By: Relevance
“…It is justified that the generation of electricity based on green energy does not produce pollutant emissions for the environment. 86,89,92 However, the SeG proposed in the project have a minor negative impact on the environment due to the CO 2 emissions embedded within. For energy systems that power EV-CS considered in this case study, the calculated CO 2 emissions values for 1 kWh energy are shown in Figure 10.…”
Section: Environmental Impact-co 2 Emissionsmentioning
confidence: 99%
“…It is justified that the generation of electricity based on green energy does not produce pollutant emissions for the environment. 86,89,92 However, the SeG proposed in the project have a minor negative impact on the environment due to the CO 2 emissions embedded within. For energy systems that power EV-CS considered in this case study, the calculated CO 2 emissions values for 1 kWh energy are shown in Figure 10.…”
Section: Environmental Impact-co 2 Emissionsmentioning
confidence: 99%
“…Recently, numerous studies have devoted particular attention to renewable and sustainable energy sources, including solar [1], wind [2], biogas [3], and hydrogen [4], as replacements for fossil fuels. Hydrogen fuel cell (HFC) is recognized as an efficient alternative energy source to rival fossil fuels in the near future because it can be practically used in portable devices, vehicles, and stationary power systems [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The dimensioning, using Homer software and, later, the simulation [9][10][11] of the starting and cooling sequences in MATLAB/Simulink T.M. 8.9 demonstrated a 69% reduction in greenhouse gas emissions, an 11% improvement in annual costs, and a 5% increase of energy efficiency compared to conventional diesel engine systems [12][13][14].…”
Section: Introductionmentioning
confidence: 99%